2016
DOI: 10.35790/ebm.4.2.2016.14615
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran kadar asam urat darah pada pekerja kantor

Abstract: Prolonged hyperuricemia is the cause of gout arthritis, which has become one of burden diseases in the wide society. Several conditions can increase hyperuricemia and one of that conditions is insulin resistance associated with decreased physical activity. People with low physical activity like office workers have a higher risk of hyperuricemia. This study was aimed to describe the level of blood uric acid among office workers. This was a descriptive study with a cross-sectional design using total sampling met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
0
4
0
10
Order By: Relevance
“…This is in contrast to the research of Meiyetriani et al (2016) that showed the majority of arthritis gout experience was in those who were working, as much as 60% compared to not working as much as 11.7%. Darmawan (2016) explains that less physical activity can cause metabolic syndrome which causes insulin resistance, leading to disorders of the excretion of uric acid. Insulin resistance causes the occurrence of oxidative phosphorylation disorders which will increase the concentration of adenosine systemic resistance, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the research of Meiyetriani et al (2016) that showed the majority of arthritis gout experience was in those who were working, as much as 60% compared to not working as much as 11.7%. Darmawan (2016) explains that less physical activity can cause metabolic syndrome which causes insulin resistance, leading to disorders of the excretion of uric acid. Insulin resistance causes the occurrence of oxidative phosphorylation disorders which will increase the concentration of adenosine systemic resistance, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Namun sebaliknya, asam urat yang terlalu tinggi justru memicu sejumlah penyakit inflamatif, sebagaimana terjadi pada penyakit kardiovaskuler (Feig; dan artritis gout (Choi et al, 2005). Kurangnya aktivitas fisik dan pola makan yang tidak seimbang dapat menyebabkan tingginya asam urat dalam darah yang mengakibatkan gangguan hiperurisemia yang akan menimbulkan penyakit artritis gout dan gout nefropati (Darmawan et al, 2016).…”
Section: Pendahuluanunclassified
“…Rata-rata kadar asam urat responden dititik ini mencapai 7,175 mg/dl yang berarti kadar asam urat telah melewati batas normal. Kadar asam urat normal pada perempuan ada dalam rentang 2-6,5 mg/dl (Darmawan et al, 2016). Hal ini menunjukkan adanya perbedaan pada kadar asam urat responden saat 15 menit setelah olahraga, dimana pada titik ini terdapat kenaikan sebesar 1,019 mg/dl dari sebelum olahraga.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…In this study, the factors that influence uric acid levels are variables that are not examined. Suggestions (Fauzi, 2018;Lohr, 2018 (Darmawan et al, 2016). Kadar asam urat dalam tubuh dihasilkan dari pembentukan purin yang merupakan salah satu unsur dari asam nukleat.…”
unclassified